From E-Government to Digital Governance: A Bibliometric Analysis of Public Sector Digital Transformation (2012–2025) - Faturachman Alputra Sudirman (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2025)
This study aims to analyze evolution, intellectual structure, and emerging research trends in e-government and digital governance literature. A bibliometric analysis was conducted using 106 journal articles indexed in Scopus between 2012 and 2025. Data were collected using specific search queries related to e-government and digital transformation in the public sector. The analysis applied the PRISMA approach for systematic selection and VOSviewer to examine publication trends, co-occurrence networks, thematic clusters, and research evolution. The results reveal a significant growth in publications, particularly after 2021, indicating increasing scholarly attention to digital transformation in the public sector. Co-occurrence analysis identified four major research clusters: (1) digital transformation and technology adoption in public services, (2) digital governance and sustainable development, (3) public administration transformation through open government and smart cities, and (4) e-government service development. The findings also show a conceptual shift from e-government as a service-oriented approach toward digital governance as a broader paradigm emphasizing integration, collaboration, public value creation, and sustainability. The study is limited to English-language open-access articles within the social sciences subject area. Future research should include cross-disciplinary datasets and comparative. The findings provide strategic insights for policymakers to design digital transformation initiatives that emphasize inclusivity, sustainability, and value-oriented governance. This study offers a comprehensive bibliometric mapping that highlights the transition from e-government to digital governance and identifies emerging research directions in public sector digital transformation.